Research influence of humidity on parameters of process separation grain lots in the pneumochannel of the machine preliminary clearing - N.S. DONTSOV; N.P. POGORELOV (Advanced Engineering Research, 2008)
Outcomes examinations with an estimation effect of damp on the basic indexes of process separation grain lots in the pneumocanal of the machine prestress clearing (MPS) of a grain material are reduced.